Knowledge and importance nursing professionals have on informed consent applied to nursing care acts - Bautista Espinel, Gloria Omaira; Ardila Rincón, Nelson Andrés; Castellanos Peñaloza, Juan Carlos; Gene Parada, Yohana (Universidad y Salud, 2017)
Introduction: Nursing acts are based on the nurse-patient relationship, respect for the dignity and autonomy of people. This implies understanding the importance and meaning from the human sphere, which is an aspect that gives an ethical sense of care practices. This reflective process deserves adequate knowledge of the actions that are necessary to obtain the informed consent. Objective: Identify the knowledge and importance that nursing professionals have about the informed consent applied in the acts of care, based on the theory of knowledge patterns. Materials and methods: A descriptive, quantitative, cross-sectional study was conducted with a sample of 221 nursing professionals, who undertook a questionnaire type Likert scale. Descriptive statistics, factorial and inferential analysis were applied for the analysis. Results: It could be seen that there was little knowledge about the use of informed consent in the participants. The variable called importance is focused on the legal, administrative and instrumental aspect of the informed consent. Conclusion: The use of informed consent should be encouraged in acts of care of the profession. The ways to explain the risks, benefits and alternatives to the patient must be reinforced as well as the ethical aspects.